Selection of patient reported outcomes questions reflecting symptoms for patients with metastatic melanoma receiving immunotherapy - Lærke K. Tolstrup; Lars Bastholt; Ann-Dorthe Zwisler; Karin B. Dieperink; Helle Pappot (SpringerOpen, 2019)
Abstract Context Toxicity-monitoring plays an important role in all cancer treatment, however, early recognition is vital for detecting and treating immune-related symptoms. Preparing a Patient Reported Outcomes tool and including melanoma patients receiving immunotherapy in the reporting of symptoms, may optimize toxicity-monitoring. Objectives The objective of this study was to identify the symptoms and their equivalent questions to include from the Patient-Reported Outcomes Common Terminology Criteria for Adverse Events (PRO-CTCAE) library for melanoma patients, receiving immunotherapy and, further, to evaluate if all relevant symptoms are covered by this tool. Methods To establish the relevant symptoms, three measures were taken. First, a literature search was carried out in three databases. Second, a chart audit was performed including medical records from melanoma patients receiving immunotherapy. Finally, the product information for the relevant immunotherapies was studied. Results Ten articles were included as a result of the literature search. As for the chart audit, a total of 37 patients (48 treatments with immunotherapy) were included. Overall, the reported symptoms from the literature review aligned with those identified in the chart audit. The examination of the product information supported the findings from review and chart audit, revealing only one additional symptom. In total, 28 PRO-CTCAE symptoms were selected comprising of 56 PRO-questions plus an additional question on blood in stool. Conclusion When preparing a Patient Reported Outcomes tool it is important that the preparatory work of selecting questions is done properly. By going through the literature, performing a chart audit, and examining the product information, the most important and relevant symptoms have been uncovered, facilitating the design of a PROquestionnaire, based on PRO-CTCAE, that fits the patient population under investigation.